Development of Green Bonds for Sustainable Finance in ASEAN - Sofiah, Siti; Gusrida, Hari; Sasongko, Hendro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to analyze the development, effectiveness, and implementation challenges of green bonds as a sustainable financing instrument in the ASEAN region, specifically in Indonesia, Singapore, Malaysia, Thailand, and Vietnam. The research uses a qualitative method with a meta-analysis, meta-synthesis, and gap analysis approach on various previous studies, regulations, and green bond issuance data in ASEAN countries. The results of the meta-analysis show that 58% of the studies found a positive influence of green bonds on sustainable financial development, while the other 42% showed varied and inconsistent results. The meta-synthesis reveals that the successful implementation of green bonds is significantly influenced by regulatory strength, government incentives, institutional capacity, and investor awareness levels. This confirms that regulatory harmonization, increased investor literacy, and strengthening the green project portfolio are strategic steps needed to accelerate the growth of green bonds in ASEAN.